Identification of m6A- and ferroptosis-related lncRNA signature for predicting immune efficacy in hepatocellular carcinoma - Xie, Hongjun; Shi, Muqi; Liu, Yifei; Cheng, Changhong; Song, Lining; Ding, Zihan; Jin, Huanzhi; Cui, Xiaohong; Wang, Yan; Yao, Dengfu; Wang, Peng; Yao, Min; et al. (Frontiers in Immunology, 2022)
Background N6-methyladenosine (m6A) methylation and ferroptosis assist long non-coding RNAs (lncRNAs) in promoting immune escape in hepatocellular carcinoma (HCC). However, the predictive value of m6A- and ferroptosis-related lncRNAs (mfrlncRNAs) in terms of immune efficacy remains unknown. Method A total of 365 HCC patients with complete data from TCGA (The Cancer Genome Atlas) database were used as the training cohort, and half of them were randomly selected as the validation cohort. A total of 161 HCC patients from ICGC (International Cancer Genome Consortium) database was used as external validation (ICGC cohort). Results We first identified a group of specific lncRNAs associated with both m6A regulators and ferroptosis-related genes and constructed prognosis-related mfrlncRNA pairs. Based on this, the mfrlncRNA signature was constructed using the LASSO analysis and Cox regression. Notably, the risk score of patients was proven to be an independent prognostic factor and was better than the TNM stage and tumor grade. Moreover, patients with high-risk scores had lower survival rates, higher infiltration of immunosuppressive cells (Macrophages and Tregs), lower infiltration of cytotoxic immune cells (natural killer cells), poorer immune efficacy (both immunophenoscore and score of Tumor Immune Dysfunction and Exclusion), higher IC50, and enrichment of the induced Treg pathway, which confirmed that mfrlncRNA signature contributed to survival prediction and risk stratification of patients with HCC. Conclusions The mfrlncRNA signature, which has great prognostic value, provides new clues for identifying “cold” and “hot” tumors, and might have crucial implications for individualized therapy to improve the survival rate of patients with HCC.